Reading the Qur’an from the Contemporary Approach of Maqāṣid al-Sharī’a (A Case Study of Non-Muslim Leadership in Indonesia) - Muhammad Mabrur Barizi (Ulumuna, 2018)
This paper examines the Qur’anic verses on leadership from the perspective of maqāṣid al-sharīʻa. There has been an assumption that the norms and practices of Islamic law are incompatible to modern ideas. The Qur’an as a major source of shari’ah is here interpreted through a system approach that includes several components, namely natural cognition, inclusiveness, interrelation of hierarchy, multi-division and meaningfulness. The analysis comprises of four stages: identifying the correlated-focus verses, identifying their meanings, exploring the maqāṣid al-sharīʻa and contextualizing it to the Indonesian context. This method will be applied to conceive of the Qur’anic verses on leadership, including non-Muslim leadership. There are six special verses discussing about this issue and seven others in general. This study shows that although there are verses that restrict non-Muslim leadership for Muslims but other, more general, verses emphasize on the capability of leadership in upholding justice and peace. The ones that stress such gerenal conditions are relevant to the Indonesian context.